Cyberdakwah: Tiktok Sebagai Media Baru - Intan Musdalifah; Nikmah Hadiati Salisah (KOMUNIDA : Media Komunikasi dan Dakwah, 2022)
The purpose of this study is to analyze and answer the phenomenon of using Tik Tok media as a forum for new Islamic communication activities. This study uses the literature method with non-participant observation and literature review. The methodology of this research analysis combines the media of Tiktok propaganda, the content of the message of da'wah, and theories related to the new media. The results of the study show the advantages and disadvantages of Islamic communication activities in cyberspace (TikTok) for preachers. TikTok media conveys da'wah messages quickly and easily, but is easier to understand. The use of TikTok as a propaganda medium has various advantages and disadvantages. On the positive side, TikTok has become a new medium of Islamic da'wah that is effective, open, accessible, and able to convey the message of Islamic teachings in various ways. On the negative side, TikTok's character is open with unclear and arbitrary information and some information in the name of Islamic teachings with a specific purpose.